2014
DOI: 10.1186/s13018-014-0059-6
|View full text |Cite
|
Sign up to set email alerts
|

Costs of staged versus simultaneous bilateral total knee arthroplasty: a population-based study of the Taiwanese National Health Insurance Database

Abstract: BackgroundBilateral total knee arthroplasty (TKA) is required for many patients. There are few studies comparing the overall costs of staged and simultaneous bilateral TKA.MethodsThe Taiwan National Health Insurance Research Database (NHIRD) was searched, and the total medical costs of 452 patients who received simultaneous bilateral TKAs were compared with those of 690 who received staged bilateral TKAs.ResultsAll categories of medical costs were lower in the simultaneous TKA group, with the exception of ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 26 publications
8
33
0
1
Order By: Relevance
“…Our results are consistent with previous studies, which have estimated the economy of simultaneous TKA or THA, compared with staged TKA or THA [2,[16][17][18][19]. A study from Taiwan demonstrated that all categories of medical costs, except for therapeutic procedure fees, were lower in the simultaneous TKA group [2].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results are consistent with previous studies, which have estimated the economy of simultaneous TKA or THA, compared with staged TKA or THA [2,[16][17][18][19]. A study from Taiwan demonstrated that all categories of medical costs, except for therapeutic procedure fees, were lower in the simultaneous TKA group [2].…”
Section: Discussionsupporting
confidence: 91%
“…Despite bilateral knee and hip arthroplasty being frequently performed, most studies paid attention to clinic outcomes, and only a few studies have been published recently on this topic. However, previous studies have not compared costs about THA, to say nothing of comparing costs when pooled both THA and TKA patients [2,7,12]. In this study, we compared the cost of simultaneous and staged procedures among TKA, THA, and their combination groups, found a signi cant difference between the two procedures in three groups.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Acute hospital LOS and total inpatient costs were lower for sim‐BTKA than staged BTKA, which is consistent with other studies, including recent studies on single‐anaesthetic BTKA that failed to distinguish between sim‐BTKA and sequential BTKA . Although a higher proportion of sim‐BTKA patients are discharged to inpatient rehabilitation which extends inpatient costs, acute hospital care is more expensive.…”
Section: Discussionsupporting
confidence: 88%
“…In haemophilia subgroup of patients, also, there has been a trend to perform multiple surgeries during a single operating session – the benefits being twofold . The costs of the factor replacement are shared for both procedures and the rehabilitation programme will be facilitated . Patients with haemophilia often suffer from multiple joint involvement (including bilateral knee arthropathy).…”
Section: Discussionmentioning
confidence: 99%